Body measurement of riding horses with a versatile tablet-type 3D scanning device - MATSUURA, Akihiro; DAN, Maiko; HIRANO, Aiko; KIKU, Yoshio; TORII, Suzuka; MORITA, Shigeru (Journal of Equine Science, 2021)
The measurement of various body dimensions of horses plays a significant role in quality improvement, genetic breeding, health, and soundness. There has been significant advancement in the technology for acquiring stereoscopic images with a three-dimensional (3D) scanner. This study aimed to validate the accuracy of body measurements obtained from stereoscopic images taken with a 3D scanner. We manually took the following body measurements for 8 riding horses: height at the withers, height at the back, height at the croup, chest depth, width of the chest, width of the croup, width of the waist, girth circumference, cannon circumference, and body length. Using a versatile tablet-type 3D scanning device, we captured a 3D image of each horse. Relative errors varied from −1.37% to 6.25%. The correlation coefficient between manual and 3D measurements was significant for all body measurements (P<0.01) except for width of the waist and cannon circumference. The low accuracy of cannon circumference (r=0.248) was due to effect of hair. A simple regression analysis of all body measurements revealed a strong correlation (P<0.001, R2=0.9994, root-mean-square error [RMSE]=1.522). Notable advantages of this methodology include high accuracy, good operability, non-contact, high versatility, and low cost. Further studies are required for the establishment of an accurate measurement methodology that can scan the whole body in a shorter time.